If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 = -7x + 2(7x + 11) Reorder the terms: -27 = -7x + 2(11 + 7x) -27 = -7x + (11 * 2 + 7x * 2) -27 = -7x + (22 + 14x) Reorder the terms: -27 = 22 + -7x + 14x Combine like terms: -7x + 14x = 7x -27 = 22 + 7x Solving -27 = 22 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -27 + -7x = 22 + 7x + -7x Combine like terms: 7x + -7x = 0 -27 + -7x = 22 + 0 -27 + -7x = 22 Add '27' to each side of the equation. -27 + 27 + -7x = 22 + 27 Combine like terms: -27 + 27 = 0 0 + -7x = 22 + 27 -7x = 22 + 27 Combine like terms: 22 + 27 = 49 -7x = 49 Divide each side by '-7'. x = -7 Simplifying x = -7
| 7(7x+1)-4x=13(3c-2) | | 1200+750=9500 | | 0.06(y-0.5)=0.06y+0.09 | | 17x^2+1=2x | | 70=5b+10 | | -6x+4(2x-15)=-50 | | (k-1)=3x^2+3x+2 | | .25(x+.4)=.1x-1.6 | | x^2+9=x+17 | | -24-3y=-6(x+2) | | 0.12x+5-0.2x=0.37x-0.4 | | 7(2x-3)+3=6(2x-3)(2x-3) | | 6(x-6)=2x+2(x-8) | | 6s-11=-2+5 | | 6(-b+6)=30-6 | | 82+13x-68=8x+49 | | 22+4b=6(1+b) | | 3x+40=7x | | 2x+65=7x+5 | | 5-7n=-8+6n | | 1-e^16-x^2=0 | | 25x=1200+9x | | 2x+7(-4x-18)=186 | | 30+.10=200 | | 3x-(15-12x)=-3(5-5x) | | 24.8+(-8.7)-13= | | 4=1/4x | | m^10+7m^5+12=0 | | T(x)=-0.85x+9.6 | | 15(3-6)=56.25 | | (2+2)-(4*4)+(8-6)= | | 6x+9=7x+1 |